AL-IJTIHĀD AL-ISTIṢLĀḤĪ AND ITS IMPACT IN CONTEMPORARY JURISTIC INFERENCE: MAJELIS TARJIH’S PERSPECTIVE OF MUHAMMADIYAH - Rachmadani, Fajar (IJISH (International Journal of Islamic Studies and Humanities), 2018)
After critically analyzing and comparing the thoughts of Islamic legal scholars on authority of unrestricted interest (maṣlaḥah al-mursalah) and its competence in juristic inference, the author concludes that both can be evidence for reasoning. Moreover, in new problems in which religious texts have not dealt with. This paper concludes that Muhammadiyah as a renewal Islamic movement has a certain council for issuing fatwās, namely Mejelis Tarjih dan Tajdid (The Council of Tarjih and Tajdid). It considers unrestricted interest as one of the evidences in juristic inference and issuing fatwās. This appears from fatwās issued by the council which are based on al-Ijtihād alistiṣlāḥī or so called unrestricted interest, including fatwā on unregistered marriage, fatwa on divorce not through the court, rely on al-ḥisāb al-falakī for determining early hijri months, fatwā on smoking, and fatwā on charity of profession. This paper is using inductive approach and its primary sources are the principles Islamic jurisprudence books. In addition, its secondary sources are the compilation of Majelis Tarjih’s fatwā, articles, journals, and all information on this topic. Furthermore, this article also considers the books on comparative school of Islamic jurisprudence.